2017
DOI: 10.1080/21641846.2017.1299079
|View full text |Cite
|
Sign up to set email alerts
|

Patients diagnosed with Myalgic encephalomyelitis/chronic fatigue syndrome also fit systemic exertion intolerance disease criteria

Abstract: Background: Myalgic encephalomyelitis/ chronic fatigue syndrome (ME/CFS) remains undiagnosed in up to 91% of patients. Recently, the United States-based Institute of Medicine (IOM) developed new diagnostic criteria, naming it systemic exertion intolerance disease (SEID). Purpose: We examined how subjects fit SEID criteria and existing ME/CFS case definitions early in their illness. Methods: A total of 131 subjects fitting 1994 Fukuda CFS criteria at the time of study recruitment completed a survey of symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Alternatively, peri-onset stressful events might act as the “straw that broke the camel's back,” accelerating a pathological process which was already underway. A hallmark feature of ME/CFS is post-exertional malaise (PEM), a severe and often prolonged exacerbation of multiple symptoms (e.g., muscle pain, fatigue, problems thinking, sore throat) which is out-of-proportion to the physical, cognitive, emotional, or positional stressors triggering it (6, 44, 91). PEM can be triggered by activities of daily life (e.g., showering, cooking, reading, etc.)…”
Section: A Gradual Onset Preceded By An Infectious Event Is the Most mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, peri-onset stressful events might act as the “straw that broke the camel's back,” accelerating a pathological process which was already underway. A hallmark feature of ME/CFS is post-exertional malaise (PEM), a severe and often prolonged exacerbation of multiple symptoms (e.g., muscle pain, fatigue, problems thinking, sore throat) which is out-of-proportion to the physical, cognitive, emotional, or positional stressors triggering it (6, 44, 91). PEM can be triggered by activities of daily life (e.g., showering, cooking, reading, etc.)…”
Section: A Gradual Onset Preceded By An Infectious Event Is the Most mentioning
confidence: 99%
“…The objective of this study was to examine the different dimensions of ME/CFS together and fill in some of these gaps, by characterizing clinical aspects of ME/CFS in detail in one cohort of subjects based in the United States. This study will also serve as a reference for other papers derived from the same cohort (44, 45) exploring relationships among immunological, genetic, microbiological, and clinical characteristics of ME/CFS. Findings from this study may inform clinical care, help generate hypotheses about etiology, pathophysiology, diagnosis, and treatment, and assist in the design and implementation of future studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study using the same questionnaire to evaluate SEID criteria, we found that 84% of subjects self-reporting ME/CFS diagnosis mainly based on Fukuda's criteria [9] met the SEID criteria [12]. Other studies on SEID criteria have reported comparable results classifying a similar percentage of subjects among ME/CFS patients (72-88%) [22,23]. Nevertheless, the diagnostic value of SEID criteria remains controversial, being considered less specific than ME criteria [22][23][24].…”
Section: Discussionmentioning
confidence: 78%
“…Other studies on SEID criteria have reported comparable results classifying a similar percentage of subjects among ME/CFS patients (72-88%) [22,23]. Nevertheless, the diagnostic value of SEID criteria remains controversial, being considered less specific than ME criteria [22][23][24].…”
Section: Discussionmentioning
confidence: 87%
“…These researchers found that by using the OI symptoms instead of neurocognitive impairment, only 2% more participants met the IOM criteria than if the criteria had only required cognitive impairment. A different approach was tried by Chu et al [ 25 ], but her team utilized a categorical response of “yes” and “no” to measure “feeling sick, uncomfortable, or fainting while standing.” In contrast to Jason et al’s [ 24 ] findings, Chu et al (2017) found that 92% of participants reported OI and 87% of participants endorsed cognitive impairment. Chu et al’s group operationalization of OI allowed for 13% more participants to meet the IOM criteria than if participants were required to endorse cognitive impairment alone.…”
Section: Discussionmentioning
confidence: 99%